Gytis Norvilas’s Poem “european litany”: The Dynamics of Text Boundaries and Structure - Salupere, Silvi; Katkuvienė, Jurgita (Semiotika, 2025)
Based on the principles and tools of structural analysis of poetic texts decribed by Juri Lotman, this article examines the poem “european litany through my god and smoke, or infidèle europe (mass for drums, triangle, and six double basses)” of one of the most prominent contemporary Lithuanian poets Gytis Norvilas (from his poetry collection sinking (grimzdimas, 2017)). As part of extensive semiotic studies of Norvilas’s poetry, this analysis outlines yet another facet of Norvilas’s poetic world, while also demonstrating the productivity of Lotman’s semiotics in the interpretation of contemporary poetry. In describing the structural principles of poetic text, Lotman reveals the fluid, dynamic boundaries of a text that produces meaning. They are related to the internal syntagmatics of textual elements which models the artistic space of the text and encompasses the internal relationships within the text and non-textual relations. Based on this, the analysis of the poem focuses on three trajectories of meaning generation: 1) description of a more general model of the artistic world of Norvilas’s poetry, reconstructed from spatial structure and archisemes, which is realized in the structure of the poem “european litany”; 2) examination of the non-textual relations created by the poem’s title and epigraph, which reveal strategies for subverting genres and the meanings they create; 3) analysis of the grammatical structure of the text based on a system of pronouns and the composition of the stanza structure. An analysis of the latter revealed the dialogic nature of the poem’s structure, demonstrating how the author’s point of view is constructed in a complex and indirect manner. The play of genres in the poem manifests itself as deformation of the litany, which transforms the “prayerful” content into a critique of the world being addressed.